The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.jcrs.2014.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of femtosecond laser–assisted arcuate keratotomy to treat irregular astigmatism after penetrating keratoplasty

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
34
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 30 publications
5
34
4
1
Order By: Relevance
“…Improvement of the UCVA and BCVA after the combined procedure was observed in the present study in comparison with the results of femtosecond laser-assisted AK for the treatment of high-astigmatism post-PKP reported by Cleary et al (22) and Fadlallah et al (23). In the present study, the mean UCVA improved from 0.95±0.24 LogMAR pre-operatively to 0.61±0.17 LogMAR postoperatively (P<0.05).…”
Section: Discussionsupporting
confidence: 78%
“…Improvement of the UCVA and BCVA after the combined procedure was observed in the present study in comparison with the results of femtosecond laser-assisted AK for the treatment of high-astigmatism post-PKP reported by Cleary et al (22) and Fadlallah et al (23). In the present study, the mean UCVA improved from 0.95±0.24 LogMAR pre-operatively to 0.61±0.17 LogMAR postoperatively (P<0.05).…”
Section: Discussionsupporting
confidence: 78%
“…Comparable to our study, Löffler et al [8] have recently reported a reduction of the magnitude of anterior corneal astigmatism in a prospective study enrolling 27 healthy corneas undergoing penetrating femtosecond laser-assisted keratotomy, with minimal effect on the magnitude of posterior corneal astigmatism. Chan et al [11] The reduction in corneal topographic astigmatism was associated with a reduction in refractive cylinder, as observed in other studies evaluating the effect of femtosecond-assisted ISAK in virgin [13], post-refractive surgery [18], and post-keratoplasty corneas [9] [10] [15]. Day and colleagues [13] found in a prospective case series including 196 eyes undergoing femtosecond laser-assisted ISAK that 0% of the eyes had a refractive cylinder of 0.50 D or less preoperatively, with an increase to 32.1% postoperatively.…”
Section: Discussionmentioning
confidence: 81%
“…In the current study, we have demonstrated that non-penetrating femtosecond laser-assisted ISAK is effective not only in terms of corneal topographic , but also after refractive surgery [18] or even in post-keratoplasty corneas with high levels of associated astigmatism [9] [10] [14] [15]. Comparable to our study, Löffler et al [8] have recently reported a reduction of the magnitude of anterior corneal astigmatism in a prospective study enrolling 27 healthy corneas undergoing penetrating femtosecond laser-assisted keratotomy, with minimal effect on the magnitude of posterior corneal astigmatism.…”
Section: Discussionmentioning
confidence: 99%
“…27 Recently, many authors reported better results using femtosecond laser technology with AK. [29][30][31] Loriaut et al 29 reported a mean CI of 0.9 of femtosecond-assisted AK in post-keratoplasty astigmatism, but 50% of eyes were overcorrected. Although the CI of FTAK was 0.63 in our study, only 3 eyes (4%) were overcorrected with FTAK, including 2 eyes that were overcorrected by less than 0.5 D (Fig.…”
Section: Discussionmentioning
confidence: 99%